Bundlers' dilemmas in financial markets with sampling investors - Milo Bianchi; Philippe Jehiel (Theoretical Economics, 2020)
We study banks' incentive to pool assets of heterogeneous quality when investors evaluate pools by extrapolating from limited sampling. Pooling assets of heterogeneous quality induces dispersion in investors' valuations without affecting their average. Prices are determined by market clearing assuming that investors cannot borrow nor short-sell. A monopolistic bank has the incentive to create heterogeneous bundles only when investors have enough money. When the number of banks is sufficiently large, oligopolistic banks choose extremely heterogeneous bundles, even when investors have little money and even if this turns out to be collectively detrimental to the banks. If in addition banks can originate low quality assets, even at a cost, this collective inefficiency is exacerbated and pure welfare losses arise. Robustness to the presence of rational investors and to the possibility of short-selling is discussed.
Keywords: C72; D53; G14; G21; 330; Complex financial products; bounded rationality; disagreement; market efficiency; sampling